Diagnosis on the consumption of single use plastic bags and its negative impact on the environment - Borda Luna, Benjamin (2021)
The objective was to diagnose the behavior of the population in Peru regarding the consumption of single-use plastic bags. For the survey, a 26-question semi-structured questionnaire was used, made up of four dimensions: primary information, consumption styles, environmental knowledge and tendency to change. The sample was 1,400 people in person and online during 2019. In relation to primary information, 3 to 5 individuals live per home; people with a university degree and without instruction prevail, made up of independent workers, the female sex being the dominant, aged 20 to 40 years. Regarding consumption styles, respondents make their purchases in retail markets and supermarkets, coming from one to two times a week, they do not carry any materials to store their purchases and they receive plastic bags from these establishments. Regarding environmental knowledge, they prefer plastic bags to carry their purchases because they have no cost. Regarding the environmental impact, they mention that they do know, but have no other option, receiving 6 to 10 bags per purchase that are disposed of for the disposal of garbage. Finally, for the tendency to change, they prefer that the establishments stop providing the bags free of charge, so as not to contaminate, preferring that reusable bags be delivered, and they are willing to pay up to 5 cents per bag. Finally, policies are required to guide consumers to the use of single-use plastic bags.